International Year of Planet Earth 2. Earth and Health — Building a Safer Canadian Environment - Rasmussen, Pat; Gardner, H.D. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY This article reviews the current state of Earth and Health research in Canada, in commemoration of International Year of Planet Earth. Canadian geoscientists play a pivotal role in identifying sources and pathways of exposure to geochemical substances that may be beneficial or detrimental to human health. Application of geoscience techniques and expertise contributes to understanding the sources and pathways of natural versus anthropogenic contaminants; bioaccumulation and biomagnification of contaminants in remote settings; and regional variability in background levels of elements and their compounds in the environment. Internationally, the relationship of earth sciences to human health has become so important that it has given rise to a new field of study termed ‘Medical Geology’. Within Canada, there are vivid examples of the impact of geological materials and processes on human health. Mineralogists, geochemists and toxicologists have started collaborating to quantify proportions of metals in soil and dirt, household dust, and playground substrates that are soluble and potentially available for absorption in the body. Other current issues include the new radon guidelines; distribution patterns of mercury in Canadian Shield lakes and reservoirs; geological sources of arsenic and fluoride in groundwater; selenium in Cretaceous sediments; exposures to airborne particles, some of which have natural sources such as windblown dust, forest-fire debris, and volcanic ash; and urban geochemistry with focus on childhood exposures to lead. Geoscience research into sources and pathways of metals and other geochemical hazards improves the accuracy and reliability of human health risk assessments that underlie risk management policies and decision-making.